2009
DOI: 10.1146/annurev-matsci-082908-145419
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory Polymer Research

Abstract: The past several years have witnessed significant advances in the field of shape memory polymers (SMPs) with the elucidation of new compositions for property tuning, the discovery of new mechanisms for shape fixing and recovery, and the initiation of phenomenological modeling. We critically review research findings on new shape memory polymers along these lines, emphasizing exciting progress in the areas of composites, novel recovery triggering, and new application developments. 445Annu. Rev. Mater. Res. 2009.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
729
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 834 publications
(757 citation statements)
references
References 90 publications
4
729
0
1
Order By: Relevance
“…); light (photo-responsive, without apparent temperature fluctuation); and, mechanical force (mechano-responsive, including impact and pressure) [2][3][4][5][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…); light (photo-responsive, without apparent temperature fluctuation); and, mechanical force (mechano-responsive, including impact and pressure) [2][3][4][5][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Figurementioning
confidence: 99%
“…[4,7,9,10,25,37,43,139,148,149], based on the principles of the above discussed working mechanisms, the performance of existing materials can be optimized by means of controlling the processing parameters in programming [113,126,150]. Figure 30 illustrates the influence of the programming temperature on shape fixity ratio (R f ) and shape recovery ratio (R r ).…”
Section: Optimizationmentioning
confidence: 99%
“…For instance, the literature search conducted by Liu et al [1] showed an almost exponential increase of publications on this topic since 1980. Numerous applications are being explored, which require the development of new compositions and structures, with new challenges to be faced, as presented in such recent reviews as by Liu et al [1], Rousseau [2] or Mather et al [3].…”
Section: Introductionmentioning
confidence: 99%
“…T he concept of shape memory polymers (SMPs) [1][2][3][4][5][6] has been known for decades [7][8][9][10][11][12][13] . In general, the polymer's shape memory (SM) effect is described and evaluated in a thermo-temporal SM cycle, where the SMP is firstly deformed at a high temperature (usually above the glass transition or melting point) and subsequently frozen upon cooling to fix the programmed temporary shape.…”
mentioning
confidence: 99%